Factors Influencing Pregnant Women’s Participation in Prenatal Classes in Magetan Regency, Indonesia - Uzza, Rofiatul; Adi, Sapto; Puspita Ratih, Suci (KnE Life Sciences, 2021)
Prenatal classes in Indonesia are government’s effort to improve the knowledge and skills of pregnant women. Several factors influence the participation of pregnant women in these classes. This research aimed to identify the factors that correlate with pregnant women’s participation in prenatal classes in several rural villages of Magetan Regency, Indonesia. This observational analytical research was performed quantitatively using a cross-sectional design. Seventy-eight pregnant women meeting the research criteria were included in this study. Data were collected through a questionnaire that has been tested through validity and reliability tests. A binary logistic regression was employed to conduct a statistical analysis. Results showed that supports from family (OR 32.40, p-value < 0.01, 95% CI 4.55–230.64) and from health workers (OR 22.53, p-value < 0.001, 95% CI 3.96–128.19) were significantly associated with the respondent’s participation in prenatal classes after controlling the potential confounding factors such as knowledge, attitudes and information availability. Keywords: maternal health, health promotion program, pregnancy, infant health